1989
DOI: 10.1093/ptj/69.9.748
|View full text |Cite
|
Sign up to set email alerts
|

Balance Performance Among Noninstitutionalized Elderly Women

Abstract: Descriptive data were collected regarding static standing balance of 71 noninstitutionalized elderly women as they performed two timed balance tests. All subjects performed the sharpened Romberg test and the one-legged stance test on each foot in four test conditions: 1) eyes open, 2) eyes closed, 3) shoes on, and 4) shoes off. Subjects were grouped and analyzed according to the following age ranges: 1) 60 to 64 years, 2) 65 to 69 years, 3) 70 to 74 years, 4) 75 to 79 years, and 5) 80 to 86 years. The best tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
0
12

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(136 citation statements)
references
References 19 publications
6
110
0
12
Order By: Relevance
“…The task is performed 3 times and the best of 3 is chosen. [60][61][62] Respiratory rate (RR) was measured three times for each participant to reduce within-session variability during baseline and immediately following the 8-week AYT. It was determined by counting the number of inhalations with a stethoscope for 30 seconds at rest and multiplying by two.…”
Section: Study Outcomesmentioning
confidence: 99%
“…The task is performed 3 times and the best of 3 is chosen. [60][61][62] Respiratory rate (RR) was measured three times for each participant to reduce within-session variability during baseline and immediately following the 8-week AYT. It was determined by counting the number of inhalations with a stethoscope for 30 seconds at rest and multiplying by two.…”
Section: Study Outcomesmentioning
confidence: 99%
“…Early detection of balance problem in the elderly will go a long way in preventing fall and its complication frequently occurring in the elderly. It will also help in limiting or preventing activity limitation or participation limitation, which is usually associated with aging (Briggs et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This test was performed as described by Briggs et al (1989). The subject assumed a heel-to-toe standing position.…”
Section: Sharpened Romberg Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, a healthy neuromuscular system to provide balance, requires sufficient muscle strength to return to the centre of gravity within the support basis when there is an imbalance between the motor response and balance. As loss of balance usually occurs in situations related to movements such as walking, it has been reported that it is necessary to achieve balance control in both dynamic and static positions [21,22].…”
Section: Postural Control and Balancementioning
confidence: 99%